2017
DOI: 10.1371/journal.pone.0181252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prey, pitcher age, and microbes on acid phosphatase activity in fluid from pitchers of Sarracenia purpurea (Sarraceniaceae)

Abstract: Carnivory in pitcher plants generally involves digestion of prey, by the plant itself, by symbionts, or both. While symbionts appear to be important in the digestion of prey in Sarracenia purpurea, the importance of pitcher-derived enzymes is less well documented. Our goal was to reduce microbial numbers in pitcher fluid in order to measure the acid phosphatase activity attributable to the pitchers themselves. Preliminary experiments indicated that various antibiotics were minimally effective at reducing micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(50 reference statements)
2
17
0
Order By: Relevance
“… * Present. References: [1] Fukushima et al, 2017 ; [2] Schulze et al, 2012 ; [3] Pavlovic, Jaksova & Novak, 2017 ; [4] Pavlovic et al, 2013 ; [5] Butts, Bierma & Martin, 2016 ; [6] Unhelkar et al, 2017 ; [7] Matušíková et al, 2005 ; [8] Michalko et al, 2013 ; [9] Jopcik et al, 2017 ; [10] Morohoshi et al, 2011 ; [11] Amagase, 1972 ; [12] Sirova, Adamec & Vrba, 2003 ; [13] Płachno et al, 2006 ; [14] Luciano & Newell, 2017 ; [15] Porembski & Barthlott, 2006 ; [16] Adlassnig, Peroutka & Lendl, 2010 ; [17] Jaffe et al, 1992 ; [18] Mithöfer, 2011 ; [19] Srivastava et al, 2011 ; [20] Hatano & Hamada, 2008 ; [21] Rottloff et al, 2016 ; [22] Takeuchi et al, 2011 ; [23] Lee et al, 2016 ; [24] Schrader et al, 2017 ; [25] Kadek et al, 2014a ; Kadek et al, 2014b ; [26] Higashi et al, 1993 ; [27] Buch et al, 2015 ; [28] Stephenson & Hogan, 2006 ; [29] Athauda et al, 2004 ; [30] Yilamujiang et al, 2017 ; [31] Eilenberg et al, 2006 ; [32] Renner & Specht, 2013 ; [33] Tokes, Woon & Chambers, 1974 ; [34] Thornhill, Harper & Hallam, 2008 . …”
Section: Digestive Enzyme Discovery Identification and Characterisatmentioning
confidence: 99%
“… * Present. References: [1] Fukushima et al, 2017 ; [2] Schulze et al, 2012 ; [3] Pavlovic, Jaksova & Novak, 2017 ; [4] Pavlovic et al, 2013 ; [5] Butts, Bierma & Martin, 2016 ; [6] Unhelkar et al, 2017 ; [7] Matušíková et al, 2005 ; [8] Michalko et al, 2013 ; [9] Jopcik et al, 2017 ; [10] Morohoshi et al, 2011 ; [11] Amagase, 1972 ; [12] Sirova, Adamec & Vrba, 2003 ; [13] Płachno et al, 2006 ; [14] Luciano & Newell, 2017 ; [15] Porembski & Barthlott, 2006 ; [16] Adlassnig, Peroutka & Lendl, 2010 ; [17] Jaffe et al, 1992 ; [18] Mithöfer, 2011 ; [19] Srivastava et al, 2011 ; [20] Hatano & Hamada, 2008 ; [21] Rottloff et al, 2016 ; [22] Takeuchi et al, 2011 ; [23] Lee et al, 2016 ; [24] Schrader et al, 2017 ; [25] Kadek et al, 2014a ; Kadek et al, 2014b ; [26] Higashi et al, 1993 ; [27] Buch et al, 2015 ; [28] Stephenson & Hogan, 2006 ; [29] Athauda et al, 2004 ; [30] Yilamujiang et al, 2017 ; [31] Eilenberg et al, 2006 ; [32] Renner & Specht, 2013 ; [33] Tokes, Woon & Chambers, 1974 ; [34] Thornhill, Harper & Hallam, 2008 . …”
Section: Digestive Enzyme Discovery Identification and Characterisatmentioning
confidence: 99%
“…With respect to P solubilisation, the key enzymes involved are acid and alkaline phosphatase [14]. Acid phosphatases are of plant origin [15], whilst bacteria, fungi, and earthworms secrete alkaline phosphatase enzymes [16]. Both enzymes, in association, facilitate the liberation of organic phosphate esters in both acid and alkaline conditions in phosphorus-deficient soils [17].…”
Section: Introductionmentioning
confidence: 99%
“…Early isolation and culturing of pitcher plant bacteria identified a range of microbial functions (Lindquist, 1975), and other studies applied genetic analysis techniques to cultured isolates (Whitman et al, 2005; Siragusa, Swenson & Casamatta, 2007) or identified particular functional groups of pitcher plant bacteria (Young, Sielicki & Grothjan, 2018). Recent studies have linked enzyme activity to bacterial functions in nutrient cycling within S. purpurea pitchers (Luciano & Newell, 2017; Bittleston et al, 2018; Young, Sielicki & Grothjan, 2018). However, despite studies of bacterial diversity, characterization of bacterial enzyme functions, the critical importance of bacteria in prey digestion and thus carbon and nutrient supply to the food web, bacteria have only recently been considered as more than a ‘black box’ in food web models (Lau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%